Impact of Mineral Dust on Summertime Precipitation Over the Taiwan Region. Issue 19 (6th October 2020) - Zhang, Yanda; Yu, Fangqun; Luo, Gan; Chen, Jen‐Ping; Chou, Charles C.‐K.
Abstract: Dust particles are effective ice nuclei and are known to affect precipitation. Here, the possible impacts of mineral dust on summertime cloud and precipitation over the Taiwan region are investigated through analysis of 25 years (1989–2013) of multiple observational and modeling data sets. Due to the unique mechanism, typhoon precipitations are excluded from this study. Statistical methods (partial correlation and stratification) are used to untangle the influences of dust from the covarying meteorological conditions (water vapor, horizontal wind, sea surface temperature, and moisture flux). The results suggest a statistically significant positive correlation between nontyphoon precipitation and the number concentration of dust particles larger than 0.5 μm ( N d ) in July and August in the regions with heavy precipitation. From clean ( N d = 0.008 cm −3 ) to dusty days ( N d = 0.2 cm −3 ), averaged ice (liquid) water paths and precipitation increase by 25% ( 20%) and 70% over the orographic region, and vertically, 30% more cloud ice content is generated at 350 hPa ( T = −20°C), enhancing the development of the mixed‐phase cloud and precipitation. The results also indicate the critical role of the atmospheric water vapor in the responses of precipitation to N d, with precipitation increasing more significantly with N d in higher water vapor circumstances. Key Points: Long‐term multiple observational and modeling data sets are used to study the correlation between mineral dust and summertime precipitation The analysis suggests a positive correlation between dust number concentration and precipitation in the orographic region The impact of mineral dust on precipitation is more significant in environments with higher water vapor concentrations